STUDY OF THE ANXIOLYTIC ACTIVITY OF ETHANOLIC EXTRACT OF ROOT OF ACORUS CALAMUSIN ALBINO MICE USING MIRRORED CHAMBER - SHIPRA KAUSHIK; HARSHWARDHAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Anxiety is classified as a form of sub-acute or chronic fear. Root of Acorus calamus has been traditionally used as an anxiolytic. The aim of the study is to assess the anxiolytic activity of ethanolic extract of the root of Acorus calamus (EEAC) by Mirrored Chamber Test on Albino mice. Methods: Albino mice of either sex were taken and divided into five groups, each consisting of 5 mice. One group was used as control, one as standard (Diazepam) and three as test groups treated with 100, 200 & 400 mg/kg of EEAC. The drugs i.e., 10 ml/kg of Normal saline for control, Diazepam 2 mg/kg (standard) and 100, 200 & 400 mg/kg EEAC (test groups) were injected intraperitoneally (i.p.), 30 mins before placing them in the center of the mirrored chamber. Latency to enter the chamber, number of entries in five minutes and total time spent in the chamber during 5 minutes test period were compared in each group. Data were statistically analyzed by one-way analysis of variance followed by multiple Dunnett’s test. Results: EEAC showed significant increase in all the parameters for the doses of 100, 200 and 400 mg/kg in a dose dependent manner. Conclusion: EEAC has anxiolytic activity.